2020
DOI: 10.1097/aud.0000000000000921
|View full text |Cite
|
Sign up to set email alerts
|

Musical Experience Offsets Age-Related Decline in Understanding Speech-in-Noise: Type of Training Does Not Matter, Working Memory Is the Key

Abstract: Objectives: Speech comprehension under “cocktail party” scenarios deteriorates with age even in the absence of measurable hearing loss. Musical training is suggested to counteract the age-related decline in speech-in-noise (SIN) perception, yet which aspect of musical plasticity contributes to this compensation remains unclear. This study aimed to investigate the effects of musical experience and aging on SIN perception ability. We hypothesized a key mediation role of auditory working memory in ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 49 publications
7
36
0
Order By: Relevance
“…Individuals with high vs. low synchrony behavior-despite strong differences in whether they received musical training and the overall years of trainingshowed no differences in the type of musical instrument they were trained on. In line with our findings, others have shown no effect of the type of musical training on auditory psychophysical measures (comparing violinist and pianists: Carey et al, 2015), or on an age-related benefit from musical training for speech perception in noise (comparing several instrument families: Zhang et al, 2020).…”
Section: Type Of Musical Instrument Training and Speech Auditory-motor Synchronizationsupporting
confidence: 92%
See 2 more Smart Citations
“…Individuals with high vs. low synchrony behavior-despite strong differences in whether they received musical training and the overall years of trainingshowed no differences in the type of musical instrument they were trained on. In line with our findings, others have shown no effect of the type of musical training on auditory psychophysical measures (comparing violinist and pianists: Carey et al, 2015), or on an age-related benefit from musical training for speech perception in noise (comparing several instrument families: Zhang et al, 2020).…”
Section: Type Of Musical Instrument Training and Speech Auditory-motor Synchronizationsupporting
confidence: 92%
“…Although, the generalizability of musical training to higher cognitive and non-music-related tasks (beyond pitch processing) has been discussed controversially ( Moreno and Bidelman, 2014 ; Ruggles et al, 2014 ; Carey et al, 2015 ), many studies report beneficial effects on auditory perception. For example, musical training has been suggested to increase auditory working memory ( Zhang et al, 2020 ), aspects of auditory scene analysis ( Pelofi et al, 2017 ), or inhibitory control ( Slater et al, 2018 ). Furthermore, many studies have reported that musical training affects speech perception in noise ( Parbery-Clark et al, 2011 ; Strait and Kraus, 2011 ; Swaminathan et al, 2015 ; Varnet et al, 2015 ; Zendel et al, 2015 ; Coffey et al, 2017a ; Puschmann et al, 2018 ; Yoo and Bidelman, 2019 ), while additional variables might affect the outcome of such a comparison ( Ruggles et al, 2014 ; Boebinger et al, 2015 ; Yoo and Bidelman, 2019 ; for a review see, Coffey et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A set of special Chinese nonsense sentences 13 , 16 were used as target ones which were translated from English nonsense sentences developed by Helfer 12 , 16 19 . For instance, the English translation of a Chinese nonsense sentence “一些条令已经翻译我的大衣” is “Some rules had translated my coat ” (the three 2-character keywords are italic) 17 . Target sentences with a naturally stable rate were spoken by a young female talker (talker A) at an average rate of 5.4 syllables/s (with the standard deviation of 0.7 syllables/s), while the duration of a sentence was about 2–3 s. The noise masker was a stream of steady-state speech-spectrum noise, whose spectrum was representative of the average spectrum of target sentences.…”
Section: Methodsmentioning
confidence: 99%
“…Speech perception becomes challenging in noisy environments and older adults (Du, Buchsbaum, Grady, & Alain, 2016; L. Zhang, Fu, Luo, Xing, & Du, 2021).…”
Section: Introductionmentioning
confidence: 99%